Rancang Bangun Aplikasi Administratif Pengelolaan Kegiatan Pelatihan pada PT. BJTI Menggunakan Administrative Workflow System - cahyo, oky dwi; Tjandrarini, A. B.; Susilo, Tegar Heru (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT Berlian Jasa Terminal Indonesia (PT BJTI) is a service company engaged in service of loading / unloading of containers. The success of PT BJTI today can not be separated from their employee training. Currenly, PT BJTI still use papper to create the documents for employee training. During the last three years, the number of stored documents reaches 1114 document. The human resources department also experienced constraints in terms of a long search time training data for the storage of training documents that stacked into one. Based on this problem, it made an administrative application management training activities using administrative workflow system (AWS). This application applies the theory of AWS to ensure the process flow can run well. Result showed that the application is able to reduce paper documents up to 100% and speed up the search process of training data. This is reflected in the time required search of training data, initially takes 5 minutes to 15 seconds after using the application.